Simulasi Pengukuran Mutu Perguruan Tinggi: Principal Component Analysis (PCA) pada Model Integrasi BANPT - COBIT - Faradillah Faradillah; Muhammad Fadhiel Alie (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
This study integrates two measurement instruments, namely the BAN PT assessment matrix as a measure of quality and COBIT 5 as a measurement of higher education IT governance through the application of Principal Component Analysis to reduce variables with the same components in order to obtain a measurement model that can accommodate IT quality and governance equally. Based on the PCA results obtained 2 Main Components with variables VMTS, Civil Service and Curriculum on Main Component Factor 1 and Build, Acquire and Implement, Deliver, Service and Support, Monitor, Evaluate, and Score on Main Component Factors 2 with a total of 44 indicator items. Furthermore, a simulation of measuring higher education accreditation was carried out with the variable using the average value. This research was conducted at a private university in South Sumatra, the simulation results obtained showed a score of 3.62 or at the "Established" level. The results of this simulation can then be used by these universities in preparing the actual accreditation process.